2020
DOI: 10.1038/s41598-020-63395-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Predicts Total Knee Replacement from Magnetic Resonance Images

Abstract: Knee Osteoarthritis (OA) is a common musculoskeletal disorder in the United States. When diagnosed at early stages, lifestyle interventions such as exercise and weight loss can slow OA progression, but at later stages, only an invasive option is available: total knee replacement (TKR). Though a generally successful procedure, only 2/3 of patients who undergo the procedure report their knees feeling "normal" post-operation, and complications can arise that require revision. This necessitates a model to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…Hip and knee arthroplasty typically involve an older and highly comorbid patient population, and these tools can be especially helpful in identifying patient-specific needs and risks within this population. Examples of how these models can enable providers to create and optimize personalized treatment plans include accurate identification of an implant from a previous surgery for revision procedures and classifying total knee arthroplasty (TKA) surgical candidates based on patient-specific risk factors [29][30][31][33][34][35][37][38][39][40][41][42]44,62]. Hyer et al demonstrated an AI/ML model which classified TKA and total hip arthroplasty patients based on surgical complexity scores [19].…”
Section: Discussionmentioning
confidence: 99%
“…Hip and knee arthroplasty typically involve an older and highly comorbid patient population, and these tools can be especially helpful in identifying patient-specific needs and risks within this population. Examples of how these models can enable providers to create and optimize personalized treatment plans include accurate identification of an implant from a previous surgery for revision procedures and classifying total knee arthroplasty (TKA) surgical candidates based on patient-specific risk factors [29][30][31][33][34][35][37][38][39][40][41][42]44,62]. Hyer et al demonstrated an AI/ML model which classified TKA and total hip arthroplasty patients based on surgical complexity scores [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our predictive models showed that T tuning the hyperparameter for the tree depths can be performed. 33 In reality, building highly accurate predictive and diagnostic models for OA requires rigorous feature engineering methods 34,35 work which is beyond the scope of this paper. We limited this initial study to the T 2 analysis of average values across compartments, however, previous studies reported that spatial assessment of the knee cartilage relaxation times using laminar and sub-compartmental analyses could lead to better and probably earlier identification of cartilage matrix abnormalities 36,37 Extraction of second-order statistical information or texture analysis 38,39 has been widely used to overcome the limitation of the average-based approaches.…”
Section: T 2 Values and Tkrmentioning
confidence: 99%
“…Thus, it is preferable for KOA patients to delay TKA and to prolong the good health of their knees. Several models concerning TKA risk in KOA patients that conducted based on clinical information are reported, whose performance could be improved with the introduction of imaging data [14][15][16][17][18]. Chan et al [14] developed a formula reflecting the decision for TKA in patients with a painful KOA based on clinical and radiographic information, while Yu et al [15] automatically extracted patient data from electronic records to allow individuals TKA risk estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al [14] developed a formula reflecting the decision for TKA in patients with a painful KOA based on clinical and radiographic information, while Yu et al [15] automatically extracted patient data from electronic records to allow individuals TKA risk estimation. Machine learning and deep learning methods were also used in building prediction models for identifying KOA patients at high risk of TKA [16][17][18]. Such models are necessitated for clinicians to pursue appropriate treatment options.…”
Section: Introductionmentioning
confidence: 99%